The Role of Influencer Marketing in Building Authentic Brand Relationships Online - Okonkwo, Ifeanyi; Namkoisse, Emmanuel (Journal of Digital Marketing and Communication, 2023)
Influencer marketing is a dynamic digital strategy that leverages social media influencers to promote products or brands to a targeted audience. It has evolved with the rise of platforms like Instagram, YouTube, and TikTok, providing individuals a stage to build substantial followings. Brands now collaborate with influencers to connect authentically with their demographics. Over time, influencer marketing has progressed from endorsements to include sponsored content, product placements, and influencer-generated material, emphasizing authenticity and trust in influencer selection. The objective of this review is to explore the dynamics of influencer marketing, from its evolution to its ethical considerations, effective campaign crafting, risk mitigation, and future trends, emphasizing its significance in the digital age.  In the influencer marketing landscape, there are various influencer types, including celebrities, micro-influencers, and nano-influencers. Celebrities offer broad reach but may lack personal connection, while micro-influencers engage specific niche audiences, and nano-influencers have hyper-local, engaged communities. Crafting effective influencer campaigns entails defining clear objectives, selecting the right influencers, creating engaging content, implementing a multi-channel approach, and fostering audience engagement. Measuring success beyond vanity metrics focuses on quantifiable outcomes for a more accurate evaluation. Mitigating risks involves addressing authenticity, regulatory compliance, audience relevance, content quality, metrics, scalability, and potential negative publicity, ensuring successful influencer partnerships. Future trends include virtual influencers and AI-driven campaigns, with influencer marketing evolving toward authenticity and long-term partnerships.